Features of the winter common wheat variety ‘Zodiak’ when cultivating it according to various forecrops and sowing time - A. S. Popov; G. V. Ovsyannikova; A. A. Sukharev; I. K. Kopman; D. M. Marchenko; I. V. Fetyukhin (Зерновое хозяйство России)
The current study was carried out in the southern part of the Rostov region in the agrotechnical crop rotation of the laboratory for grain cultivation technology. The purpose of the study was to determine the effect of such factors as a forecrop and sowing time on productivity and grain quality of the winter common wheat variety ‘Zodiak’. During the study, there was found that the variety ‘Zodiak’ produced up to 9.70 t/ha. There was established that the high adaptability of the variety ‘Zodiak’ made it possible to obtain high yields at different sowing dates, however, there was a tendency to form maximum productivity when sowing at the optimal time for the area (20 and 30 of September). There was found that the large productivity of the crop sown in black fallow was ensured by the number of productive stems (up to 596 pcs/m2) and productivity per head (number of kernels per head up to 31.3 pcs., grain weight per head up to 1.42 g). For all forecrops in the variant with a late sowing time, there was a decrease in number of kernels per head (by 6.2–22.9 %) and mass of grain per head (by 1.7–11.7 %) compared with earlier sowing dates. Biochemical analysis has shown that when sown in black fallow and after peas, the yielded grain had the maximum protein per-centage on average up to 14.1 % and 13.3 %, respectively. There has been established that the variety ‘Zodiak’ could form high-quality grain even when it was sown after sunflower (with 12.3–12.6 % of protein and 22.5–23.5 % of gluten). The best economic indicators in the cultivation of the variety ‘Zodiak’ were obtained when it was sown in black fallow, with up to 191 % of profitability, up to 77993 rubles/ha of conditional net income.